PENGARUH INOVASI SOSIAL TERHADAP KINERJA KEUANGAN UMKM DENGAN KINERJA SOSIAL DAN LINGKUNGAN SEBAGAI VARIABEL MEDIASI DI KOTA PALANGKA RAYA - Cahaya Tamba, Ruth; Sarlawa, Rita; Sri Widyaningsih, Dhina; Muliyani, Agustina (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Micro, Small, and Medium Enterprises (MSMES) play a strategic role in the regional economy, yet they still face challenges in sustainably improving their financial performance. This study aims to analyze the influence of social innovation on the financial performance of MSMEs, with social and environmental performance as mediating variables in the city of Palangka Raya. This study employed a quantitative approach with explanatory research methods. Data were collected through questionnaires from 100 MSMES and analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS 3.0. The results showed that social innovation had a positive and significant effect on financial performance, social performance, and environmental performance. Social and environmental performance were also shown to have a positive effect on financial performance. The results of the mediation test indicated that social performance mediated the relationship between social innovation and financial performance through complementary mediation (partial mediation), while environmental performance did not act as a mediating variable. This study emphasizes the importance of developing socially oriented social innovation as a strategy to improve the financial performance and sustainability of MSMEs.